The Relationship between Attitude towards Extramarital affairs with the Feeling of Inferiority, Locus of Control, and Practice of Religious Beliefs in Wives of Addicted Men - Khalili, Reza; Bahmani, Bahman; Khanjani, Mohammad Saeed; Vahedi, Mohsen (Journal of Assessment and Research in Applied Counseling (JARAC), 2021)
Aim: The present study aimed to determine the relationship between attitudes toward extramarital affairs with the feeling of inferiority, locus of control, and practice of religious beliefs in wives of addicted men. Methods: The present study was descriptive and correlational, and its statistical population consisted of all women participating in Naranan population meetings in the 5th and 9th districts of Tehran. Among whom, we selected 120 individuals using the convenience sampling method. To collect data, we used the extramarital affair attitude questionnaire (Whatley, 2006), feeling of inferiority source (Khodadadi and Bahrami, 2012), Locus of Control Scale (Rotter, 1966), and practice of religious beliefs questionnaire (Golzari, 2000). We also used inferential statistical methods (spearman’s correlation) to analyze data. Results: The results indicated that there were positive and significant relationships between attitudes towards extramarital affairs with the feeling of inferiority and also between attitudes towards extramarital affairs and locus of control in wives of addicts (P=0.05). There was not any significant relationship between attitudes towards extramarital affairs and the practice of religious beliefs (P>0.05). Conclusion: Therefore, feeling of inferiority and locus of control affected attitudes toward extramarital affairs, but the present study did not find any effect of practicing religious beliefs on attitudes towards extramarital affairs.